Analysis of maxillary anterior teeth proportion in relationship with lower facial height and malocclusion - Gyawali, Rajesh; Singh, Varun Pratap (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Maxillary anterior tooth to tooth proportion has a special value in dental esthetics. This study aimed to assess the apparent proportion of maxillary anteriors and possible association with lower anterior facial height and malocclusion type. Materials & Methods: One-hundred and sixty samples with well aligned maxillary dentition were selected and the lower anterior facial height was measured with digital caliper. Molar relationship was examined and intraoral frontal photograph was taken for digital measurement of tooth proportion. The ratio of maxillary canine to lateral and lateral to central incisors were measured and compared between gender and the sides. These ratios were further compared among various malocclusion type using ANOVA and its association with lower anterior facial height was evaluated with Pearson’s correlation. Results: Most of the samples had Class I molar relationship (70%) followed by Class II (23%) and Class III (7%). The mean lower anterior facial height was 62.82mm and ratio of maxillary lateral to central incisor and canine to lateral incisor was 0.68 and 0.76 respectively. No statistically significant difference was found when the ratio was compared between the gender and the sides. These ratios were statistically different from the golden ratio and has no significant correlation with lower anterior facial height. These mean ratios were also found similar across the malocclusion type. Conclusion: Ratio of apparent dimension of maxillary canine to lateral incisor and lateral to central incisor was different from the golden ratio and showed no association with lower anterior facial height and malocclusion type.